The Ideology of Capitalism (AmeriQuests, 2012)
This manuscript addresses from a range of perspectives the crisis of capitalism, claiming that it's failures are not an accident or a result of the actions of a few unprincipled men. Rather, it is a harbinger of things to come – loss of employment due to technology and globalization, a world without the myth of constant growth, tension between ethnic and national groups which seek to tilt the scale in favour of their group, a constant need for more radical technology and a fear of its unavoidable frightening side. Its one possible positive effect will occur if there emerges a new willingness to question the assumptions of capitalism and the political correctness of identity politics, shifts in both attitude and behavior that the author deems unlikely at the current juncture or in the foreseeable future.TABLE OF CONTENTSI. INTRODUCTIONII. THE CURRENT CRISISIII. THE “SMALL GOVERNMENT” DEFENSE OF CAPITALISMIV. DOES THE HISTORY OF THE 20TH CENTURY VINDICATE CAPITALISMV. CAPITALISM AND SOVIET MARXISMVI. THE NEW MANVII. INTERNATIONALISM AND GLOBALIZATIONVIII. THE ALIENATED MANIX. ALIENATION AND FAMILY STRUCTUREX. CAPITALISM AND DEMOCRACY XI. THE DOUBLETHINK OF CAPITALISMXII. CULTURE AND CAPITALISMXIII. THE “CONTRACT” DEFENCE OF CAPITALISMXIV. THE POSITIVE SIDE OF LIBERAL CAPITALISMXV. INSTITUTIONAL TAKE-OVERXVI. CAPITALISM AND THE TOWER OF BABELXVII. THE NEW SYSTEMXVIII. POLITICAL STRUCTURE IN THE NEW SYSTEMXIX. THE NEW SYSTEM AND INDIVIDUAL HAPPINESSXX. COURTS AND JUDICIAL REVIEW IN THE NEW SYSTEM XXI. PHILOSOPHY, SCIENCE AND MORALITY IN THE NEW SYSTEMXXII. WHY NOT “REAL” SOCIALISMXXIII. HOW IS A NEW SYSTEM TO BE CREATEDXXIV. EDUCATIONXXV. DISOBEDIENCE AND WITHDRAWALXXVI. REFORM OF THE LEFTXXVII. LABOUR UNIONS AS A SPECIAL INTEREST LOBBYXXVIII. MULTICULTURALISM AND CULTUREXXIX. CULTURE AND DEMOGRAPHYXXX. A BOOT IN THE FACE OF MANKIND FOREVERXXXI. CONCLUSION
Keywords: law; marxism; radicalism; Quebec; Canada